تحديات القياس والإفصاح المحاسبي عن المسؤولية البيئية - مزيمش, أسماء; عوادي, عبد القادر; قويدر, محمد الطيب (جامعة الوادي University of Eloued, 2018)
تهدف هذه الورقة البحثية إلى التعرف على المحاسبة البيئية والتحديات التي تحول دون تطبيقها، فنظرا للدور الكبير لها في الحفاظ على البيئة فقد أصبحت محل اهتمام الباحثين والمهنيين من أكاديميين وحكومات ومنظمات، وقد حرصت المحاسبة البيئية منذ ظهورها على دمج البعد البيئي مع البعد الاقتصادي لأجل انتاج قوائم وتقارير مالية ملمة بالأداء الكلي للمؤسسة، مما تسمح باعطاء نظرة مفصلة وواضحة عن الوضعية المالية للمؤسسة. وقد توصلت الدراسة إلى أن المحاسبة البيئية تلعب دورا هاما في المؤسسات كونها أداة فعالة في دعم المركز التنافسي لها، إلا أنها لازالت تواجه عدة صعوبات فيما يخص عملية القياس والإفصاح عنها. This paper aims to identify environmental accounting and the challenges that prevent it from being applied, in view of the important role of environmental accounting in preserving the environment, it has become the focus of researchers and professionals from academics, governments and organizations. since its inception, environmental accounting has focused on integrating the environmental dimension with the economic dimension to produce financial statements and reports relevant to the overall performance of the institution, allowing for a detailed and clear view of the financial position of the institution. The study found that environmental accounting plays an important role in institutions as an effective tool in supporting its competitive position, but it still faces several difficulties in the process of measurement and disclosure.
مقال
Keywords: مسؤولية بيئية، محاسبة بيئية، إفصاح بيئي; environmental responsibility, environmental accountig, environmental disclosure.